SOSIALISASI PEMBERDAYAAN UMKM “UMKM BANGKIT BERSINERGI” - Erin Soleha; Erina Rulianti; Fiqih Maria (Jurnal Pengabdian Masyarakat, 2022)
MSMEs are one of the factors that affect the rate of economic growth, but many problems are faced, namely the licensing of their businesses. Sukamahi Village has several Micro, Small and Medium Enterprises (MSMEs) that have developed but there are still many that do not have permits such as not having a Business Identification Number (NIB) and Micro Small Business Permit (IUMK). The author made observations and interviews with business owners before holding this MSME empowerment socialization. The results of this service open the mindset of business owners about the importance of having business legality.